Magnetic resonance imaging characteristics of benign macrocephaly in children - (:unkn) unknown (DECKER PERIODICALS INC, 1999)
Benign macrocephaly of infancy is a common problem in the child neurology practice. The radiologic features of this entity are not well defined. In most of the previous studies, macrocephalic patients were evaluated by computed tomography. To define the radiologic characteristics of this entity, 20 children with macrocephaly with normal neurologic examinations were enrolled in the study. All the patients were evaluated by magnetic resonance imaging studies. Sixty-five percent of patients had enlargement of the subarachnoid space and 35% of patients had megalencephaly. None of the patients had subdural collections. The mean age of patients with enlargement of the subarachnoid space was found to be younger than those with megalencephaly. The cases with parental histories of macrocephaly demonstrated both enlargement of the subarachnoid space and megalencephaly. Our results suggest that the radiologic finding of benign macrocephaly can be both enlargement of the subarachnoid space and megalencephaly.
Keywords: EXTERNAL HYDROCEPHALUS; SUBDURAL COLLECTIONS; SUBARACHNOID SPACE; NATURAL-HISTORY; DIFFERENTIATION; ATROPHY; BRAIN; SIZE; US